ANALISIS KUALITAS PELAYANAN TAMU PADA HOTEL CABIN CABANG SUTOMO YOGYAKARTA - Sugiyah; Suparman HL (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
Hotels are important facilities that cannot be separated from the tourism sector. The roleof the hotel is not only a place to stay for tourists, but also as a place to carry out officeand educational activities such as meetings, seminars, marketing presentations, so that thegrowth of hotel development is increasing. Quality of service in the field of hospitalityservices is one of the considerations that are often used by guests in choosing hotels. Goodservice quality is closely related to the implementation of SOPs as a basis for carrying outtasks.This qualitative descriptive study begins with the implementation of the StandardOperating Procedure (SOP) for guest services at the Sutomo Hotel Yogyakarta branch,the quality of guest services at the Yogyakarta Branch Sutomo Hotel, constraints facedand how to overcome them in providing guest services. Guest SOP services frompredetermined reservations, check-in until guests check out fully. Quality of service hasan impact on the sale of rooms sold. The results of the data show that during the periodJanuary - August 2018 the average number of rooms sold was 519 rooms / month.Based on the results of the SWOT analysis with IFAS and EFAS matrices obtained strengthvalues (Streghts) - Weaknesses (weakness) = 2.24 -1.43 = 0.81 and opportunity values(Opportunity) - Threats (Treaths) = 2.21 - 0.99 = 1, 22. Thus Cabin Sutomo Hotel has aQuadrant I position so the strategy that needs to be done to increase the number of hotelguests is an aggressive strategy. This is a situation that benefits Cabin Sutomo Hotelbecause it has the power and opportunity, so that it can make the most of the opportunitiesavailable and support aggressive improvement policies. In the SWOT matrix, it was foundthat the right strategy was the S-O strategy, namely by increasing friendly and fast serviceand continuing to innovate hotel products, this was supported by the increasing numberof domestic and foreign tourists, so that they were potential guests at Cabin Sutomo hotel.